PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA KARYAWAN GENERASI Z DI PT DIGDAYA BERKAH INDONESIA - Anbrilla; Christantius Dwiatmadja; Ardiani Ika Sulistyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to examine the effect of Leadership Style and Compensation on Job Satisfaction, with Motivation as an intervening variable, among Generation Z employees at PT. Digdaya Berkah Indonesia, Semarang Regency, Central Java. The research employed a quantitative approach, distributing closed-ended questionnaires to 57 Generation Z employees at the company. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results indicate that Leadership Style does not have a significant effect on Job Satisfaction, while Compensation has a positive and significant effect on Job Satisfaction. Leadership Style has a positive and significant effect on Motivation, and Motivation in turn has a significant effect on Job Satisfaction. Moreover, there is a very strong relationship between Compensation and Motivation.